2008
DOI: 10.1128/aac.00084-08
|View full text |Cite
|
Sign up to set email alerts
|

ramR Mutations Involved in Efflux-Mediated Multidrug Resistance in Salmonella enterica Serovar Typhimurium

Abstract: In the sequenced genome of Salmonella enterica serovar Typhimurium strain LT2, an open reading frame (STM0580) coding for a putative regulatory protein of the TetR family is found upstream of the ramA gene. Overexpression of ramA results in increased expression of the AcrAB efflux pump and, consequently, multidrug resistance (MDR) in several bacterial species. The inactivation of the putative regulatory protein gene upstream of ramA in a susceptible serovar Typhimurium strain resulted in an MDR phenotype with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
153
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 34 publications
10
153
0
1
Order By: Relevance
“…In this study, we identified five substrates of the RamR protein, including berberine, crystal violet, dequalinium, ethidium bromide and rhodamine 6G. Similar approaches in crystallizing the TetR family regulators with multiple drugs have been also reported in QacR 20 , TtgR 21 ARTICLE six amino acid substitutions in RamR that are related to bacterial drug resistance, including T18P, R46N, R46P, Y59H, M84I and E160D 15,17,23 . As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this study, we identified five substrates of the RamR protein, including berberine, crystal violet, dequalinium, ethidium bromide and rhodamine 6G. Similar approaches in crystallizing the TetR family regulators with multiple drugs have been also reported in QacR 20 , TtgR 21 ARTICLE six amino acid substitutions in RamR that are related to bacterial drug resistance, including T18P, R46N, R46P, Y59H, M84I and E160D 15,17,23 . As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Its binding site covers essential features of the ramA promoter, including the À 10 conserved region, the transcriptional start site of ramA and two 7-bp inverted repeats 16 . Various types of mutations in ramR and the ramR-ramA intergenic region were identified in multidrug-resistant strains of S. typhimurium, other S. enterica serovars and K. pneumoniae, which result in increased expression of ramA and an increase in efflux-mediated multidrug resistance 15,17,18 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, little is known about rob and its contribution to antibiotic resistance in Salmonella. More recently, RamA, which displays close homology to MarA and is absent from E. coli, has been implicated in MDR in Salmonella and other bacteria (1,16,19,42). Overexpression of ramA has been associated with increased expression of acrB in Salmonella and other Enterobacteriaceae (1,19,42).…”
mentioning
confidence: 99%